Acute Intermittent Porphyria: Predicted Pathogenicity of HMBS Variants Indicates Extremely Low Penetrance of the Autosomal Dominant Disease. Issue 11 (5th September 2016) - Chen, Brenden; Solis‐Villa, Constanza; Hakenberg, Jörg; Qiao, Wanqiong; Srinivasan, Ramakrishnan R.; Yasuda, Makiko; Balwani, Manisha; Doheny, Dana; Peter, Inga; Chen, Rong; Desnick, Robert J.
Abstract : Acute intermittent porphyria (AIP) is an autosomal dominant inborn error of heme biosynthesis, which heterozygotes can have life‐threatening neurovisceral acute attacks. Based on genomic/exomic databases, we estimate that 1 in ∼1, 780 Caucasians has a pathogenic hydroxymethylbilane synthase ( HMBS ) mutation. However, only ∼1% of these heterozygotes experience acute attacks. This extremely low penetrance suggests that other genetic and environmental factors predispose to acute attacks. ABSTRACT: Acute intermittent porphyria results from hydroxymethylbilane synthase ( HMBS ) mutations that markedly decrease HMBS enzymatic activity. This dominant disease is diagnosed when heterozygotes have life‐threatening acute attacks, while most heterozygotes remain asymptomatic and undiagnosed. Although >400 HMBS mutations have been reported, the prevalence of pathogenic HMBS mutations in genomic/exomic databases, and the actual disease penetrance are unknown. Thus, we interrogated genomic/exomic databases, identified non‐synonymous variants (NSVs) and consensus splice‐site variants (CSSVs) in various demographic/racial groups, and determined the NSV's pathogenicity by prediction algorithms and in vitro expression assays. Caucasians had the most: 58 NSVs and two CSSVs among ∼92, 000 alleles, a 0.00575 combined allele frequency. In silico algorithms predicted 14 out of 58 NSVs as "likely‐pathogenic." In vitro expression identified 10 out of 58 NSVs as likely‐pathogenic (seven predicted in silico), which together with two CSSVs had a combined allele frequency of 0.00056. Notably, six presumably pathogenic mutations/NSVs in the Human Gene Mutation Database were benign. Compared with the recent prevalence estimate of symptomatic European heterozygotes (∼0.000005), the prevalence of likely‐pathogenic HMBS mutations among Caucasians was >100 times more frequent. Thus, the estimated penetrance of acute attacks was ∼1% of heterozygotes with likely‐pathogenic mutations, highlighting the importance of predisposing/protective genes and environmental modifiers that precipitate/prevent the attacks.